Beyond the Business Case: Different Models of Including People with Disabilities at Work - Justin Lee; Mathew Mathews; Wong Fung Shing; Zhuang Kuansong (Disability Studies Quarterly, 2017)
When not done properly, policies or interventions that claim to be 'inclusive' can be patronizing or even oppressive. Through interviews and focus groups with employers, service providers and the disability community in Singapore, we helped to articulate what counts as ideal or sensible inclusion of people with disabilities at work. Against those that might seek to mainstream disability wherever it exists, our findings suggest that enclaved spaces for work serve an important function despite charges of being exclusionary. Some enclaves operate as 'work villages' that provide a protected, familiar space to accommodate unique needs while others serve as 'diversity incubators' that provide scalable lessons for more mainstream contexts. Within the Singapore context, policymakers largely operate within a 'business case' paradigm that focuses on incentivizing employers and an 'industrial model' of vocational assessment and job placement. While this has a role to play, we demonstrate the importance of attending to the neglected 'moral case' for hiring people with disabilities.
Keywords: Employment policies; Inclusion; Diversity; Disability; Singapore